Nutritive value of the broiler litter based on sodium hidroxide treated rice straw and rice hulls for sheep - Barros, Nelson Nogueira; Bonnecarrere, Luiz Maria; Lopes, Juarez Marbini (Pesquisa Agropecuaria Brasileira, 2014)
Three levels (0, 6 and 12 percent) of NaOH treatment of rice straw and rice hull used as bedding on the nutritive value of broiler litter was studied in sheep. In the 2 x 3 factorial design, 18 sheep (3 in each of the groups) were used, digestibility of dry matter, organic matter, crude fibre and gross energy increased with increase of NaOH concentration on rice hull litter. For rice straw litter, reduction of these components was observed with the exception of crude fibre where increase in digestibility was observed with increase of NaOH from zero to 6 percent. Nitrogen digestibility of both litters decreased (P<0.05) with NaOH level from zero to 6 percent; and in rice hull litter a further increase was observed with increase of NaOH from 6 to 12 percent For rice hull litter, digestible dry matter, protein, and energy intake were higher (P<0.05) at 12% than at zero percent NaOH, and increase in digestible matter was directly proportional to increase in NaOH level. The intake levels of these parameters for rice straw litter were not significantly (P<0.05) only in rice hull litter from zero to 12% NaOH, although nonsignificant increases proportional to increase in NaOH level were observed in general.